Essential dynamics on different biological systems: DNA-bending protein Fis, DNA-tvMyb1 transcriptional factor and BACE1 enzyme - Gutiérrez, Lucas J. (2012)
Proteins and enzymes poses a non-covalent 3D structure and therefore their intrinsic flexibility allows the existence of an ensemble of different conformers which are separated by a low-energy barrier. These ranges of available conformers for proteins in solution are due to the relative movements among the different domains. Domain motions are important for a variety of protein functions, including catalysis, regulation of activity, transport of metabolites, formation of protein assemblies, and cellular locomotion. Considering the importance of these conformational changes it is obvious that the different techniques to evaluate these behaviours are very important in order to understand the biological effects. In the present chapter we report molecular dynamics (MD) trajectories analyzed by essential dynamics method on three different molecular systems of biological interest: i) DNA-bending protein Fis (Factor for Inversion Stimulation), ii) DNA-tvMyb1 (Trichomonas vaginalis transcriptional factor) and iii) the BACE1 (beta site amyloid cleaving enzyme 1). Although the general structural characteristics for the above systems are well known, comparatively little information is available about their flexibility and dynamics. This is in part due to difficulties with obtaining such information experimentally. Thus, our primary interest was the comparison between the unligated and the complexed state, because the corresponding conclusions may reveal motions of functional relevance.